2019
DOI: 10.2147/idr.s213958
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rapid diagnosis of neonatal sepsis by PCR for detection of 16S rRNA gene, while blood culture and PCR results were similar in <em>E.coli</em>-predominant EOS cases</p>

Abstract: Purpose To determine the bacteriological pattern and antibiotic susceptibility of bacterial isolates causing neonatal sepsis in Qena University Hospitals and compare polymerase chain reaction (PCR) and blood culture results in a trial for rapid diagnosis. Patients and methods Blood samples from 75 clinically suspected cases of neonatal sepsis were subjected to identification of bacteria and determination of their antibiotic sensitivity through blood culture, and rapid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
4
14
0
2
Order By: Relevance
“…In our study, neonatal sepsis was predominant in males (57.5 %) which is comparable to that observed in other studies carried by Kung et al 18 ; Hammoud et al 19 and EL-Amir et al 15 who found that males represent 52.8, 54.9% and 53.3% respectively. None of the previous studies found a significant difference between males and females in neonatal sepsis, which is similar to the present results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, neonatal sepsis was predominant in males (57.5 %) which is comparable to that observed in other studies carried by Kung et al 18 ; Hammoud et al 19 and EL-Amir et al 15 who found that males represent 52.8, 54.9% and 53.3% respectively. None of the previous studies found a significant difference between males and females in neonatal sepsis, which is similar to the present results.…”
Section: Discussionsupporting
confidence: 91%
“…Anwar et al 21 reported that neonatal sepsis was diagnosed in 53.8% of their neonates delivered also by C.S. Nehal et al 22 and EL-Amir et al 15 showed that neonatal sepsis occurs more frequently in neonates delivered by normal vaginal delivery with percentage of 70% and 65.3% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon title and abstract review, 1368 studies were excluded, and 119 were subjected to full-text review. Of these, 100 were excluded because valid data could not be extracted, and the remaining 19 articles were included in our study [12,13,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All studies used a prospective study design to avoid inappropriate exclusion (Figure 2). Five studies did not specify whether patients were continuously enrolled or not [25,26,[28][29][30]. The remaining studies specified continuous enrollment.…”
Section: Study Characteristicsmentioning
confidence: 99%